A statistical review: why average weighted accuracy, not accuracy or AUC?. Issue 2 (3rd July 2021) - Jiang, Yunyun; Pan, Qing; Liu, Ying; Evans, Scott
Abstract : Sensitivity and specificity are key aspects in evaluating the performance of diagnostic tests. Accuracy and AUC are commonly used composite measures that incorporate sensitivity and specificity. Average Weighted Accuracy (AWA) is motivated by the need for a statistical measure that compares diagnostic tests from the medical costs and clinical impact point of view, while incorporating the relevant prevalence range of the disease as well as the relative importance of false-positive versus false-negative cases. We illustrate the testing procedures in four different scenarios: (i) one diagnostic test vs. the best random test, (ii) two diagnostic tests from two independent samples, (iii) two diagnostic tests from the same sample, and (iv) more than two diagnostic tests from different or the same samples. The impacts of sample size, prevalence, and relative importance on power and average medical costs/clinical loss are examined through simulation studies. Accuracy has the highest power while AWA provides a consistent criterion in selecting the optimal threshold and better diagnostic tests with direct clinical interpretations. The use of AWA is illustrated on a three-arm clinical trial evaluating three different assays in detecting Neisseria gonorrhoeae and Chlamydia trachomatis in the rectum and pharynx.